Journeys erased by time : the rediscovered footprints of travellers in Egypt and the Near East - Cooke, Neil, 1947- (Archaeopress Publishing Ltd., 2019)
Early travellers in Egypt and the Near East made great contributions to our historical and geographical knowledge and gave us a better understanding of the different peoples, languages and religions of the region. Travellers in this volume are a mixture of rich and poor, bravely adventuring into the unknown, not knowing if would ever return home.